Fracture-based interface model for NSM FRP systems in concrete - Coelho, Mário Rui Freitas (2016)
This paper introduces a numerical simulation tool using the Finite Element Method (FEM) for near-surface mounted (NSM) strengthening technique using fibre reinforced polymers (FRP) applied to concrete elements. In order to properly simulate the structural behaviour of NSM FRP systems there are three materials (concrete, FRP and the adhesive that binds them) and two interfaces (FRP/adhesive and adhesive/concrete) that shall be considered. This work presents the major details of a discontinuous-based constitutive model which aims at simulating NSM FRP interfaces implemented in the FEMIX FEM software. This constitutive model was adapted from one available in the literature, originally employed for fracture simulation in meso-scale analyses of quasi-brittle materials, which is based on the classical Flow Theory of Plasticity combined with fracture mechanics concepts. The most important features of the implemented constitutive model are the consideration of both fracture modes I and II and the possibility of performing 2D and 3D analysis. In the end, results based on FEM simulations are presented with the aim of investigating the soundness and accuracy of the constitutive model to simulate NSM FRP systems’ interfaces.